1992
DOI: 10.1007/bf02253593
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effect of carbamazepine in the elevated plus-maze: possible role of adenosine

Abstract: In order to extend previously reported observations with other animal models of anxiety, the effect of carbamazepine (CBZ) was presently measured in rats placed on the elevated plus-maze. Intraperitoneal injection of CBZ (5-40 mg/kg) increased the percentage of open arm entries as well as the percentage of time spent on the open arms of the maze, without affecting the total number of arm entries. This effect is characteristic of anxiolytic drugs. The inhibitor of adenosine neuronal uptake papaverine (5-40 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…It has been reported that benzodiazepine, the most widely used anxiolytic agent, blocks adenosine uptake (35,36) and decrease adenosine A 1 receptor binding capacity in vivo at doses of clinical relevance (37). In addition, a direct involvement of adenosine in regulating affective state has been suggested by the finding that papaverine, an inhibitor of adenosine uptake, causes anxiolytic effects (38). In the present studies, to detect the anxiolytic effect of FR194921, the social interaction test and elevated plus-maze test were used as relevant animal models of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that benzodiazepine, the most widely used anxiolytic agent, blocks adenosine uptake (35,36) and decrease adenosine A 1 receptor binding capacity in vivo at doses of clinical relevance (37). In addition, a direct involvement of adenosine in regulating affective state has been suggested by the finding that papaverine, an inhibitor of adenosine uptake, causes anxiolytic effects (38). In the present studies, to detect the anxiolytic effect of FR194921, the social interaction test and elevated plus-maze test were used as relevant animal models of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…A study showing that BZDs prevent NBTI binding revealed ENT1 as a specific target of these drugs (Hammond et al, 1981). This is consistent with the reduced anxiety-like behavior in ENT1 knockout mice and the anxiolytic action of adenosine uptake inhibitor papaverine (Zangrossi et al, 1992). Given their structural similarities with adenosine, it is not surprising that BZDs have also been shown to interact with adenosine receptors in some cases.…”
Section: Benzodiazepines and Adenosine Signalingmentioning
confidence: 59%
“…Of the several equilibrative and concentrative transporters expressed in the brain, ENT1 appears to be central to the regulation of anxious states. Some of the first evidence in support of this idea came from a study demonstrating that pharmacological inhibition of adenosine uptake by papaverine was anxiolytic in the elevated plus maze test (Zangrossi et al, 1992). This study also suggested that inhibition of adenosine uptake may be a mechanism of the anxiolytic drug carbamazepine, as its actions were inhibited by adenosine receptor antagonist aminophylline (Zangrossi et al, 1992).…”
Section: Ent1mentioning
confidence: 99%
See 2 more Smart Citations